Coal Ash Characteristic from Bukit Asam as Raw Material for Ceramics Production - Pulung Karo-Karo; Simon Sembiring (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2008)
This study was carried out to characterize coal ash obtained from Bukit Asam, Tarahan Lampung, after the samples were sintered at various temperatures ranging from 900C - 1300C. The characteristics of the investigated samples included density, porosity, hardness, structure and microstructure. The results indicated that porosity decreased with increasing sintering temperature, while density and hardness increased with increasing temperature. The x-ray diffraction (XRD) study revealed that the main crystalline phase was silicon dioxide (SiO2), with the minor constituents of CaSiO2, MgSiO3, FeSiO4 and Ca12Al14O33. SEM investigations clearly demonstrated the presence of a fine crystallised phase dispersed in the microstructure.